2019
DOI: 10.5194/bg-16-1361-2019
|View full text |Cite
|
Sign up to set email alerts
|

Reduced phosphorus loads from the Loire and Vilaine rivers were accompanied by increasing eutrophication in the Vilaine Bay (south Brittany, France)

Abstract: Abstract. The evolution of eutrophication parameters (i.e., nutrients and phytoplankton biomass) during recent decades was examined in coastal waters of the Vilaine Bay (VB, France) in relation to changes in the Loire and Vilaine rivers. Dynamic linear models were used to study long-term trends and seasonality of dissolved inorganic nutrient and chlorophyll a concentrations (Chl a) in rivers and coastal waters. For the period 1997–2013, the reduction in dissolved riverine inorganic phosphorus (DIP) concentrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 112 publications
(169 reference statements)
3
21
0
Order By: Relevance
“…Phaeocystis blooms have been reported in the Somme Bight (Lamy et al, 2006;Lefebvre et al, 2011), while Dinophysis (dinoflagellates) and Pseudo-nitzschia (diatoms) are the dominant harmful algae in the Seine Bight (Cugier et al, 2005a;Garnier et al, 2019;Ménesguen et al, 2019). Whereas most of the rivers have shown a decrease in phosphorus in the last two decades (Romero et al, 2013), leading to a negative P-ICEP, as found here, algal biomass increased (diatoms and dinoflagellates) with a shift in the peak in the Vilaine Bight (Ratmaya et al, 2019), mostly due to N fluxes brought by the Loire River, which flows northwards with the currents (Ménesguen et al, 2018a(Ménesguen et al, , 2019 and to internal sources from sediments (Ratmaya et al, 2019). No strong eutrophication problems have been reported off the Loire estuary, in the North Biscay Bay, without major changes during the last two decades, in contrast to the North of France (Gohin et al, 2019).…”
Section: Coastal Eutrophication Potentialsupporting
confidence: 65%
See 3 more Smart Citations
“…Phaeocystis blooms have been reported in the Somme Bight (Lamy et al, 2006;Lefebvre et al, 2011), while Dinophysis (dinoflagellates) and Pseudo-nitzschia (diatoms) are the dominant harmful algae in the Seine Bight (Cugier et al, 2005a;Garnier et al, 2019;Ménesguen et al, 2019). Whereas most of the rivers have shown a decrease in phosphorus in the last two decades (Romero et al, 2013), leading to a negative P-ICEP, as found here, algal biomass increased (diatoms and dinoflagellates) with a shift in the peak in the Vilaine Bight (Ratmaya et al, 2019), mostly due to N fluxes brought by the Loire River, which flows northwards with the currents (Ménesguen et al, 2018a(Ménesguen et al, , 2019 and to internal sources from sediments (Ratmaya et al, 2019). No strong eutrophication problems have been reported off the Loire estuary, in the North Biscay Bay, without major changes during the last two decades, in contrast to the North of France (Gohin et al, 2019).…”
Section: Coastal Eutrophication Potentialsupporting
confidence: 65%
“…These estuaries receive nutrient deliveries from the upper river basins with different land uses and population densities (Table 2): for example, the Seine, Vilaine, Loire, and Charente river basins are dominated by agricultural activities, sustaining a large proportion of the national livestock and/or production of crop agriculture (Billen and Garnier, 2007;Ménesguen et al, 2018a;Ratmaya et al, 2019). The percentages of different land use types for each basin are presented in Table 2.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, P control may be effective in many lakes, but still allow N export to downstream ecosystems. Controlling P can exacerbate N export to N‐limited downstream systems because it reduces the uptake, sedimentation, denitrification and burial of N in upstream lakes and rivers (Elmgren & Larsson, ; Finlay, Small, & Sterner, ; Paerl, ; Ratmaya et al, ). Graneli, Wallstrom, Larsson, Graneli, and Elmgren () reached a similar conclusion regarding the movements of N and P through bays and into the open area of the Baltic Sea.…”
Section: Managing Nutrients In Complex and Linked Stream‐lake‐marine mentioning
confidence: 99%